2023
DOI: 10.7150/ijbs.85285
|View full text |Cite
|
Sign up to set email alerts
|

FABP5 suppresses colorectal cancer progression via mTOR-mediated autophagy by decreasing FASN expression

Abstract: Lipid metabolism plays an important role in the occurrence and development of cancer, in particular, digestive system tumors such as colon cancer. Here, we investigated the role of the fatty acid-binding protein 5 ( FABP5 ) in colorectal cancer (CRC). We observed marked down-regulation of FABP5 in CRC. Data from functional assays revealed inhibitory effects of FABP5 on cell proliferation, colony formation, migration, invasion as well as tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The antitumor activity of FASN attaches great significance in its prospect of being a promising therapeutic strategy for CRC. Intriguingly, Ye et al [ 40 ] recently found that fatty acid-binding protein 5 degrades FASN; however, this process ultimately promotes lipid accumulation and inhibits mTOR signaling, which facilitates cell autophagy. Taken together, lipid metabolism, especially fatty acid metabolism, plays a fundamental role in CRC growth, metastasis and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor activity of FASN attaches great significance in its prospect of being a promising therapeutic strategy for CRC. Intriguingly, Ye et al [ 40 ] recently found that fatty acid-binding protein 5 degrades FASN; however, this process ultimately promotes lipid accumulation and inhibits mTOR signaling, which facilitates cell autophagy. Taken together, lipid metabolism, especially fatty acid metabolism, plays a fundamental role in CRC growth, metastasis and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason for this is that we based our analysis on mRNA levels, while other factors such as post-transcriptional mechanisms may also influence the effect of ALKBH5 on COAD prognosis. The role of ALKBH5 in COAD reported in the literature is also controversial [ [26] , [27] , [28] ]. Therefore, further experimental studies are required to confirm it.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ABL1 gene regulates cytoskeletal dynamics and is linked to tumor drug resistance and cell migration ( 36 , 37 ). FASN encodes a fatty acid synthase that catalyzes the conversion of acetyl coenzyme A and malonyl coenzyme A to palmitate ( 38 ). Overexpression and hyperactivity of FASN are typically associated with malignant cells.…”
Section: Discussionmentioning
confidence: 99%